# NATIONAL UNIVERSITY OF SINGAPORE

SEMESTER 2, 2013/2014
MA1521 Calculus for Computing Tutorial Solution 3
1. (a)
d
dx
_
xsin
−1
1
x
−3 cos
−1
(2 lnx)
_
= sin
−1
1
x
+
x
_
1 −
1
x
2
·
−1
x
2

−3
_
1 −4 ln
2
x
·
2
x
= sin
−1
1
x

1

x
2
−1
+
6
x
_
1 −4 ln
2
x
.
(b)
d
dx
_
cos 2x
sin 2x + 3
_
=
−2 sin 2x · (sin 2x + 3) −cos 2x · 2 cos 2x
(sin 2x + 3)
2
=
−6 sin 2x −2(sin
2
2x + cos
2
2x)
(sin 2x + 3)
2
=
−6 sin 2x −2
(sin 2x + 3)
2
.
(c) ln
_
e
x

cos 2x
(1 + 2x)
4
_
= ln(e
x
) + ln

cos 2x −ln(1 + 2x)
4
= x +
1
2
ln cos 2x −4 ln|1 + 2x|.
d
dx
ln
_
e
x

cos 2x
(1 + 2x)
4
_
=
d
dx
_
x +
1
2
ln cos 2x −4 ln |1 + 2x|
_
= 1 +
1
2
·
−2 sin 2x
cos 2x

4 · 2
1 + 2x
= 1 −tan2x −
8
1 + 2x
.
(d)
d
dx
_
tan
−1
(x
4
) =
1
2
_
tan
−1
(x
4
)
·
1
1 + (x
4
)
2
· 4x
3
=
2x
3
(1 + x
8
)
_
1 + tan
−1
(x
4
)
.
(e) Let y = x
−sinx
2
. Then ln y = −sin x
2
ln x. Diﬀerentiate with respect to x:
dy
dx
·
1
y
= −cos x
2
· 2x · ln x + (−sin x
2
) ·
1
x
.
Then
dy
dx
= −x
−sinx
2
_
2xln x cos x
2
+
sin x
2
x
_
.
(f)
d
dx
5
xlnx
= 5
xlnx
ln 5 ·
_
1 · lnx + x ·
1
x
_
= 5
x lnx
ln5 (ln x + 1).
(g)
d
dx
log
x+1
(x −1) =
d
dx
ln(x −1)
ln(x + 1)
=
1
x−1
· ln(x + 1) −ln(x −1) ·
1
x+1
ln
2
(x + 1)
=
(x + 1) ln(x + 1) −(x −1) ln(x −1)
(x
2
−1) ln
2
(x + 1)
.
1
MA1521 CALCULUS FOR COMPUTING TUTORIAL SOLUTION 3 2
2. (a) Diﬀerentiate the equation with respect to x:
1 · y
2
+ x · 2y
dy
dx
+ 3x
2
· y + x
3
·
dy
dx
= 2 + 5
dy
dx
.
Then (2xy + x
3
−5)
dy
dx
= 2 −3x
2
y −y
2
; and hence
dy
dx
=
2 −3x
2
y −y
2
2xy + x
3
−5
.
(b) Diﬀerentiate the equation with respect to x:
e
y cos x
_
dy
dx
· cos x + y · (−x)
_
=
1
x
+ 2
dy
dx
.
Then
dy
dx
(e
y cos x
cos x −2) =
1
x
+ y sin xe
y cos x
; hence
dy
dx
=
xy e
y cos x
+ 1
x(e
y cos x
cos x −2)
.
(c) Diﬀerentiate the equation with respect to x:
1
1 + y
2
dy
dx
+
2
1 + x
2
y
2
_
1 · y + x ·
dy
dx
_
= 0.
Then
dy
dx
_
1
1 + y
2
+
2x
1 + x
2
y
2
_
= −
2y
1 + x
2
y
2
; hence
dy
dx
= −
2y(1 + y
2
)
1 + x
2
y
2
+ 2x(1 + y
2
)
.
3. (i)
dy
dx
=
dy/dt
dx/dt
=
−e
−t
e
−2t
−2t e
−2t
=
−e
t
1 −2t
.
d
2
y
dx
2
=
d
dx
_
−e
t
1 −2t
_
=
dt
dx
·
d
dt
_
−e
t
1 −2t
_
=
1
dx/dt
· (−1)
e
t
(1 −2t) −e
t
(−2)
(1 −2t)
2
=
−1
e
−2t
−2t e
−2t
e
t
(3 −2t)
(1 −2t)
2
= −
e
3t
(3 −2t)
(1 −2t)
3
.
(ii) Since the tangent line is vertical, we have
dx
dy
=
1
dy/dx
=
1 −2t
−e
t
= 0; that is,
t = 1/2. Then x =
1
2
e
−2×
1
2
=
1
2e
.
The equation of the tangent line is thus given by x =
1
2e
.
4. Diﬀerentiate the equation with respect to x: 2(x − y)
_
1 −
dy
dx
_
+ 4 = 0; that is,
dy
dx
=
x −y + 2
x −y
. Then
dy
dx
¸
¸
¸
(0,1)
=
0 −1 + 2
0 −1
= −1.
Therefore, the tangent line at (0, 1) is y = −1(x − 0) + 1 = −x + 1; and the normal
line at (0, 1) is y =
−1
−1
(x −0) + 1 = x + 1.
5. The slope of the line y = x + 17 is 1. Let
dy
dx
= 3x
2
+ 12x + 10 = 1. Then x = −1 or
x = −3.
(i) If x = −1, then y = 3; the tangent line at (−1, 3) is y = (x −(−1)) + 3 = x + 3.
(ii) If x = −3, then y = 5; the tangent line at (−3, 5) is y = (x −(−3)) + 5 = x + 8.
6. f

(x) = 6x
2
−10x + 4 = 2(3x + 1)(x −2).
MA1521 CALCULUS FOR COMPUTING TUTORIAL SOLUTION 3 3
(−∞, −1/3) (−1/3, 2) (2, ∞)
f

(x) + − +
f(x) ր ց ր
f
′′
(x) = 12x −10 = 2(6x −5).
(−∞, 5/6) (5/6, ∞)
f
′′
(x) − +
f(x) down up
7. (a) Let f(x) = e
tan x
. Then f

(x) = e
tan x
sec
2
x. For x near
π
4
,
f(x) ≈ f
_
π
4
_
+ f

_
π
4
__
x −
π
4
_
= e + 2e
_
x −
π
4
_
.
Since 46

=
π
4
+
π
180
, we have
e
tan 46

≈ e + 2e ·
π
180
= e
_
1 +
π
90
_
.
(b) Let f(x) = tan
−1
x. Then f

(x) =
1
1 + x
2
. For x near 1,
f(x) ≈ f(1) + f

(1)(x −1) =
π
4
+
1
2
(x −1).
Then tan
−1
(1.02) ≈
π
4
+
1
2
×0.01 =
π
4
+
1
100
.
8. (a) Let f(x) =
x + 5
x + 2
= 2. Then x = 1. Since f

(x) = −
3
(x + 2)
2
and f

(1) = −
1
3
,
(f
−1
)

(2) =
1
f

(1)
= −3.
(b) Let f(x) = e
x
−2e
−x
. Then f(ln2) = 1. Since f

(x) = e
x
+ 2e
−x
and f

(ln 2) = 3,
(f
−1
)

(1) =
1
f

(ln2)
=
1
3
.
9. (a) If 0 < x < 3, then f

(x) = 4 −2x. Let f

(x) = 0. Then x = 2.
If 3 < x < 6, then f

(x) = −1.
lim
x→3

f(x) −f(3)
x −3
= lim
x→3

4x −x
2
−3
x −3
= lim
x→3

(x −3)(1 −x)
x −3
= −2.
lim
x→3
+
f(x) −f(3)
x −3
= lim
x→3
+
6 −x −3
x −3
= 1.
Therefore, f

(3) = lim
x→3
f(x) −f(3)
x −3
does not exist.
Hence, x = 2 and x = 3 are critical numbers of f.
(0, 2) (2, 3) (3, 6)
f

(x) + − −
MA1521 CALCULUS FOR COMPUTING TUTORIAL SOLUTION 3 4
Therefore, f has a local maximum at x = 2, and neither a local maximum nor a
local minimum at x = 3.
(b) f

(x) =
e
2x
(2x −1)
x
2
. Let f

(x) = 0. Then x =
1
2
, the critical number of f.
(0,
1
2
) (
1
2
, ∞)
f

(x) − +
Therefore, f has a local minimum at x = 1/2.
(c) f

(x) = 22(2x −3)
10
. Let f

(x) = 0. Then x = 3/2, the critical number of f.
(−∞,
3
2
) (
3
2
, ∞)
f

(x) + +
Therefore, f has neither a local maximum nor a local minimum at x = 3/2.
10. (a) f

(x) =
4
(x + 1)
2
. f

(x) = 0 on (0, 10), so f has no critical numbers on (0, 10).
Compare f(0) = −4 and f(10) = 6/11, we see that f has the absolute maximum
6/11 at x = 10 and the minimum −4 at x = 0.
(b) f

(x) =
3x(x −6)
(x −3)
2
. Let f

(x) = 0. Then x = 0 or x = 6 (rejected). So x = 0 is
the only critical number of f on [−2, 2].
Compare f(−2) = −
12
5
, f(0) = 0 and f(2) = −12, we see that f has the absolute
maximum 0 at x = 0 and the minimum −12 at 2.
(c) Note that lim
x→3

f(x) = −∞and lim
x→3
+
f(x) = ∞. Hence, f has neither the absolute
maximum nor the minimum.
(d) f

(x) = 6x
2
−30x−36 = 6(x +1)(x−6). Let f

(x) = 0. Then x = −1 and x = 6.
These are the critical numbers of f.
Compare f(−2) = 7, f(−1) = 30, f(6) = −313 and f(9) = −70, we see that f
has the absolute maximum 30 at x = −1 and the minimum −313 at x = 6.
11. (a) Let f(x) = x
n
. Then
f

(x) = lim
h→0
(x + h)
n
−x
n
h
= lim
h→0
x
n
+
_
n
1
_
x
n−1
h +
_
n
2
_
x
n−2
h
2
+· · · + h
n
−x
n
h
= lim
h→0
_
n
1
_
x
n−1
h +
_
n
2
_
x
n−2
h
2
+· · · + h
n
h
= lim
h→0
__
n
1
_
x
n−1
+
_
n
2
_
x
n−2
h +· · · + h
n−1
_
= nx
n−1
+ 0 +· · · + 0 = nx
n−1
.
MA1521 CALCULUS FOR COMPUTING TUTORIAL SOLUTION 3 5
(b) Let f(x) =

ax
2
+ b. Then
f

(x) = lim
h→0
_
a(x + h)
2
+ b −

ax
2
+ b
h
= lim
h→0
(a(x + h)
2
+ b) −(ax
2
+ b)
h(
_
a(x + h)
2
+ b +

ax
2
+ b)
= lim
h→0
a(2xh + h
2
)
h(
_
a(x + h)
2
+ b +

ax
2
+ b)
= lim
h→0
a(2x + h)
_
a(x + h)
2
+ b +

ax
2
+ b
=
2ax
2

ax
2
+ b
=
ax

ax
2
+ b
.
(c) Let f(x) = sin x. Then
f

(x) = lim
h→0
sin(x + h) −sin x
h
= lim
h→0
sin xcos h + cos xsin h −sin x
h
= sin x lim
h→0
cos h −1
h
+ cos x lim
h→0
sin h
h
= sin x lim
h→0
_

sin
h
2
h
2
sin
h
2
_
+ cos x lim
h→0
sin h
h
= sin x · 0 · 1 + cos x · 1 = cos x.
12. (fgh)

= [(fg)h]

= (fg)

h + (fg)h

= (f

g + fg

)h + fgh

= f

gh + fg

h + fgh

.
In general, if f
1
, f
2
, . . . , f
n
are diﬀerentiable functions, then
(f
1
f
2
· · · f
n
)

= f

1
f
2
· · · f
n
+ f
1
f

2
· · · f
n
+· · · + f
1
f
2
· · · f

n
.